A longitudinal study of depressive symptoms and delinquency among Chinese left-behind children. (July 2021) - Lei, Huijie; Zhang, Qinghua; Wang, Zhi; Shao, Jingjin
Highlights: The present study identified the trajectories of depressive symptoms and delinquency in Chinese left-behind children over a three-year period. There were no significant changes in LBC's depressive symptoms. The trajectory of LBC's delinquency showed a decrease over time and differed across parental migration status and gender. Compared with father-only migration LBC, mother-only migration LBC reported significantly higher initial levels of depressive symptoms and delinquency. Abstract: This study sought to identify the developmental trajectories of depressive symptoms and delinquency in Chinese left-behind children (LBC) over a three-year period, a topic that is less often studied. Overall, 578 Chinese LBC ( M age = 10.63 years; boys = 53.1%) were tested three times on their depressive symptoms and delinquency from grades four through six. Unconditional latent growth modeling revealed no linear change in LBC's depressive symptoms, whereas there was a linear decrease over time in LBC's delinquency. Multiple-group models revealed that the pattern of change in LBC's delinquency differed across parental migration status and gender. Moreover, mother-only migration LBC showed higher initial depressive symptoms and initial delinquency levels than father-only migration LBC. The results provided a more accurate developmental picture by charting patterns of stability and change among Chinese LBC's depressive symptoms and delinquency in the context of parental migration.